Mesenteric cystic lymphangioma in an adult female - a case report - Kanwal, Motia; Jamal, Shahid; Wasim, Hafsa; Naval, Amat ul; Tariq, Nehaj (International Journal of Pathology, 2026)
Background: Lymphangiomas are benign vascular proliferations composed of malformed lymphatics, located in the head, neck, and axilla. Incidence in adults and at the retroperitoneal location is rare. Case presentation: We present a 34-year woman with a 7-day history of abdominal distention, colicky pain, and vomiting. Physical examination shows a non-tender, diffusely enlarged abdomen and absent bowel sounds. She underwent a magnetic resonance imaging (MRI), which confirmed 18.0 x 14.3 x 8.5 cm, multi-loculated mass extending along the mesentery of the small intestine. On histopathological examination cystic lymphangioma was the final diagnosis. Cystic lymphangioma is an unusual lesion associated with genetic and chromosomal abnormalities. Radiological investigations play a key role in pre-operative diagnosis. Final diagnosis can be obtained only after histopathological evaluation. Conclusion: This report adds to current knowledge on this pathology in atypical sites by providing thorough insights into clinical aspects, MRI results, and the histopathological correlation.